Evaluation of seismic vulnerability of multi-storeyed buildings having columns of different heights in a storey using pushover analysis - Sengupta, Amlan K.; Sarkar, Shubhayan (Journal of Structural Engineering, 2024)
The variation of the height of the columns in a storey of a multi-storeyed building increases their vulnerability to seismic forces. Assessment of seismic vulnerability of buildings can be carried out by various approaches. In this paper, an approach based on pushover analysis was used for generating vulnerability indices. The indices quantify the deficiencies in lateral load resistance and lateral drift of a building, storey drift, and the performance ranges of the hinges formed in the beams and columns. First, a regular mid-rise reinforced concrete building was analysed to evaluate the vulnerability indices. Next, the study investigated the effects of increased height of the open ground storey, foundations on sloping levels, split-level floors, and partial height infill walls in similar buildings. It was observed that the increase in vulnerability due to the variation of the height of the columns in a storey could be quantified by the indices for lateral load resistance, storey drift, and the performance of the columns in a storey.